Crystal structure of 3-(p-chlorophenyl)-5-methyl-2-(8-quinolinyl)-4-thiazolidinone, C19H16ClN2OS - Öztürk, S; Aygün, M; Öcal, N; Yolaçan, Ç; Fun, HK (R OLDENBOURG VERLAG, 2000)
C19H16ClN2OS, orthorhombic, Pca2(1) (No. 29), a = 8.1148(1) Angstrom, b = 19.1264(2) Angstrom, c = 21.7702(2) Angstrom. V = 3383.0 Angstrom(3). Z = 8, R-gt(F) = 0.069, wR(ref)(F-2)= 0.188, T = 293 K.
Keywords: Crystallography